2019
DOI: 10.1111/ecin.12855
|View full text |Cite
|
Sign up to set email alerts
|

A Monetary Business Cycle Model for India

Abstract: A New Keynesian monetary business cycle model is constructed to study why monetary transmission in India is weak. Our models feature banking and financial sector frictions as well as an informal sector. The predominant channel of monetary transmission is a credit channel. Our main finding is that base money shocks have a larger and more persistent effect on output than an interest rate shock, as in the data. The presence of an informal sector hinders monetary transmission. Contrary to the consensus view, finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…5 We show that the incidence of a contractionary …scal consolidation being expansionary now depends on the value of , the parameter denoting the relative superiority of government consumption vis-a-vis private consumption in utility. 6 When is low, a negative government spending shock increases private consumption and e¤ective consumption. The marginal utility from e¤ective consumption falls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 We show that the incidence of a contractionary …scal consolidation being expansionary now depends on the value of , the parameter denoting the relative superiority of government consumption vis-a-vis private consumption in utility. 6 When is low, a negative government spending shock increases private consumption and e¤ective consumption. The marginal utility from e¤ective consumption falls.…”
Section: Resultsmentioning
confidence: 99%
“…In the experiments we conduct later on, we arbitrarily set factor income taxes to be 10 times higher than the baseline case 6. Consistent with the empirical literature, we restrict 0 < < 1 ( seeAmbler and Paquet (1996), andBarro (1981)).…”
mentioning
confidence: 99%
“…WALR -Fresh Rupee Loans was introduced during January 2015 to September 2016 with 5 basis points and continues in the FIT regimes. (13), 48-60, July-September, 2022 market and the corporate bond market with AAA-5-year, AAA-10-Year G-sec market are showing downturn from 3 rd October 2019 and wide variation in FIT (bps) is observed.…”
Section: Analysis Of Transmission Mechanism Of Monetary Policy In Indiamentioning
confidence: 96%
“…The challenges to effective transmission of monetary policy include policy induced abrasions like interest rate subventions, loan waivers, slow adjusting savings instruments and credit allocations (Lahiri and Patel, 2016). Similarly, Banerjee and others have observed that large dominance of informal credit sector is found to be the hindrance in the process (Banerjee et al, (2018). Shelja Bhatia (2019) in her work has observed that an expansionary monetary policy produces negative and significant impact on the Tier-I capital asset ratio of banks.…”
Section: Literature Reviewmentioning
confidence: 98%
“…With the change in its policy target to IT, now the question arises that, given India’s low-income level where households spend a substantial part of their income on food and fuel, can the RBI accurately forecast its inflation path so as to contain it within a predefined range. This is because food and fuel inflation are volatile, given the fact that India is heavily dependent on monsoon and crude import for its food and fuel needs, respectively (Banerjee et al, 2020; Bhattacharya & Sen Gupta, 2018; Pattanaik et al, 2020). Moreover, a large part of the Indian economy is in the informal sector that makes monetary transmission difficult (Anand et al, 2016; Benes et al, 2017; Kulshreshtha, 2011).…”
Section: Introductionmentioning
confidence: 99%